Fragments d'un antifonari de l'ofici diví de Besiers (Tarragona, Arx. Hist. Arxid., Frag. 19/1) - Gros i Pujol, Miquel dels Sants (Miscel·lània litúrgica catalana, 2009)
The importance of the studied fragments of an Offices Antiphonary lies in its probable datation in the first quarter of 10th century, and in its procedence from Saint Nazarie Cathedral at Beziers. They are, thus, the first written witness of an Offices Antiphonary belonging to the ancient region of the Narbonensis. They also show us a kind of liturgical book where antiphons and responsoria are located in the corresponding places following the order of celebration of the Divine Office, together with the hymns of every festivity. Thus, they are to be taken as an important step in the formation of future breviaries.